Application Of The K-Means Algorithm in Clustering Medical Records Of BPJS Participants At Bhayangkara Hospital In Bengkulu - Wahyu Rizki Rasuanto; Devi Sartika; Dimas Aulia Trianggana (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Grouping is to separate labels from unknown data and grouping is expected to be able to identify data groups to then be labeled as desired. Cluster analysis is a multivariate analysis technique to find and organize information about variables so that they can be relatively grouped into homogeneous groups or